The RNAA Program Enhances the OR Team - Kress, Jack (Operating Room Nurses Association of Canada Journal, 1994)
Working in the operating room (OR) requires the expertise of numerous specialties involved in perioperative patient care. This is especially true for a tertiary care hospital which provides a broad spectrum of patient care services. As reﬂected in theSt. Boniface General Hospital (SBGH) mission statement, the goal of the hospital is to promote excellence and high quality patient care.